Pengaruh Electronic Word Of Mouth, Social Media Marketing Dan Brand Ambassador Terhadap Keputusan Pembelian Produk Erigo - Muhammad Syah Naufaly Aziz; Eri Bukhari; M Fadhli Nursal (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Developments in digital technology have changed the marketing landscape, creating new opportunities for brands to reach consumers more effectively. Erigo, as an Indonesian fashion brand that continues to grow, utilizes modern marketing strategies such as Electronic Word of Mouth (eWOM), Social Media Marketing, and Brand Ambassador to attract the attention of the younger generation. This research aims to: (1) analyze the influence of eWOM on Erigo product purchasing decisions, (2) evaluate the influence of Social Media Marketing on Erigo product purchasing decisions, (3) identify the influence of Brand Ambassadors on Erigo product purchasing decisions, and (4) explore the influence a combination of these three strategies on purchasing decisions. The research used quantitative methods with data collected through online questionnaires from 171 respondents from the 2021 Management Study Program students at Bhayangkara University, Jakarta Raya. Data were analyzed using SPSS. The research results show that eWOM builds consumer trust through positive reviews, Social Media Marketing strengthens consumer emotional involvement, and Brand Ambassadors create a positive image that influences loyalty. Collectively, these three strategies have a significant influence on purchasing decisions for Erigo products. This research emphasizes the importance of integrating digital strategies and personalization in building consumer relationships in the modern era. These findings provide strategic insights for fashion brands and other industry players who want to leverage digital marketing to increase competitiveness